A Pipeline Strategy for Grain Crop Domestication. Issue 3 (1st May 2016) - DeHaan, Lee R.; Van Tassel, David L.; Anderson, James A.; Asselin, Sean R.; Barnes, Richard; Baute, Gregory J.; Cattani, Douglas J.; Culman, Steve W.; Dorn, Kevin M.; Hulke, Brent S.; Kantar, Michael; Larson, Steve; et al.
Abstract : In the interest of diversifying the global food system, improving human nutrition, and making agriculture more sustainable, there have been many proposals to domesticate wild plants or complete the domestication of semidomesticated orphan crops. However, very few new crops have recently been fully domesticated. Many wild plants have traits limiting their production or consumption that could be costly and slow to change. Others may have fortuitous preadaptations that make them easier to develop or feasible as high‐value, albeit low‐yielding, crops. To increase success in contemporary domestication of new crops, we propose a pipeline approach, with attrition expected as species advance through the pipeline. We list criteria for ranking domestication candidates to help enrich the starting pool with more preadapted, promising species. We also discuss strategies for prioritizing initial research efforts once the candidates have been selected: developing higher value products and services from the crop, increasing yield potential, and focusing on overcoming undesirable traits. Finally, we present new‐crop case studies that demonstrate that wild species' limitations and potential (in agronomic culture, shattering, seed size, harvest, cleaning, hybridization, etc.) are often only revealed during the early phases of domestication. When nearly insurmountable barriers were reached in some species, they have been (at least temporarily) eliminated from the pipeline. Conversely, a few species have moved quickly through the pipeline as hurdles, such as low seed weight or low seed number per head, were rapidly overcome, leading to increased confidence, farmer collaboration, and program expansion.